THE ROLE AND SIGNIFICANCE OF SACRED PLACES AND SHRINES IN THE ETHNOCULTURE OF THE UZBEK PEOPLE - Jumayeva Shoira Berdiyarovna (Modern American Journals, 2025)
This article analyzes the concept of ziyarat, the history of studying sacred sites and shrines in Uzbekistan, as well as the pilgrimage rituals associated with these sacred places and shrines of the Uzbek people. In preparing the article, extensive use was made of materials from ethnological field research conducted within the Tashkent oasis.
Keywords: Place of pilgrimage, mentality, national value, Islamic religion, holy place, Zangi-ata, patriotism, culture, ritual, nature.